Safeguarding women and children from abuse. (1st March 2011) - Browne, K; Butchart, A; Penhale, B; Phillips, C; Harwin, N
Abstract : Preventing violence to women and children in the home; a review of the literature/Interventions to support victims of domestic violence: The 'Safety in numbers' project/Preventing sexual violence to young women and children/Evidence based policy and interventions to support adult victims of sexual violence/Harmful traditional practices and their impact on health and social services in the UK.